Sensory Discrimination in Neural Networks of Dissociated Cortical Culture - Goletiani, Cezar; Nino Nebieridze; Raphael Kalandadze; Khatia Nadirashvili; David Songulashvili (International Journal of Formal Sciences: Current and Future Research Trends, 2021)
For the acquisition and discrimination of sensory information, the nervous system comprises a variety of structural and functional instruments. These processes occur in accordance with the brain’s physical nature and involve many of its labyrinths. On the other hand, the brain’s complexity may pose a challenge in determining the correct mechanisms. Answering the question of why cerebral circuitry prefers some sensory stimuli over others could help us understand how we identify diversity in the world. Modeling the neuronal network in the dissociated cortical culture (DCC) homed on a multielectrode array (MEA) may help to tackle the problem and give an easier setting for research. This in vivo-like in vitro system of around 100000 neuronal and glial cells eventually build simplified but realistic neural structure and persist to exist for about two months on MEA. That allows to follow and measure structural and functional refinement and the potential for calculations and coding of information in the newly developed neural circuits as well as to understand the role of activity at the single neuron level that determines effective behavior. Following a month of in vitro development of DCC, pairs of electrodes were employed to simulate a variety of sensory inputs using various types of electric stimulation. Single, paired-pulse ((PP; 20 ms interstimulus interval) and 1, 5, 10, 20, and 50 Hz 300 mV stimuli of 1 s duration were repeated after every 20 s or at a random time interval. All channels that exhibited appropriate level of activity were monitored. Experiments revealed that registered channels tended to respond solely to one of the stimulus paradigms, creating or enhancing activity while suppressing responses to other stimuli. The most effective stimulus paradigm was PP stimuli in most cases, however specific cases indicated the efficiency of other stimulus paradigms as well. Even higher frequency stimuli had a chance to be beneficial in situations where low frequency stimuli were generally more effective. Both tonic and burst features were present in multicellular and single-unit responses. Many cases pointed to a phenomena that academics rarely pay attention to: replies that took more than 300 ms. They drew our attention since they showed selectivity to stimulator patterns as well. We revealed instant and delayed evoked responses that were not present before certain stimuli were administered, which may be regarded as gradual steps of sensory information processing by neural networks. Simultaneously, frequent exposure to the favored stimuli increased the occurrence of immediate reactions that demonstrated synaptic plasticity for memory formation. Data shows that DCC’s small neural networks are highly sensitive to physical characteristics of sensory input, allowing sensory discrimination.